Self-regulation and Beyond: Affect Regulation and the Infant–Caregiver Dyad - Taipale, Joona (Frontiers in Psychology, 2016)
In the available psychological literature, affect regulation is fundamentally considered in terms of self-regulation, and according to this standard picture, the contribution of other people in our affect regulation has been viewed in terms of socially assisted self-regulation. The present article challenges this standard picture. By focusing on affect regulation as it unfolds in early infancy, it will be argued that instead of being something original and fundamental, self-regulation developmentally emerges from the basis of a further type of affect regulation. While infants’ capacities in recognizing, understanding, and modifying their own affective states is initially immature and undeveloped, affect regulation is initially managed by the other: it is initially the self, and not the other, that plays the role of an assistant in affect regulation. To capture this phenomenon, the concepts of ”auto-matic”, ”hetero-matic”, and ”altero-matic” affect regulation will be introduced and their interrelations elaborated. By showing how the capacity of affective self-regulation, which is characteristic to maturity, is developmentally achieved by internalizing regulative functions that, at the outset of development, are managed by the caregiver, it will be argued that that altero-matic affect regulation is an autonomous type of affect regulation and the developmental basis for self-regulation.